Impact of recycled aggregate properties on concrete performance. Issue 1 (1st February 2023) - Zaharieva, R; Dimitrov, G
Abstract: One of the ways for construction sector to contribute to sustainability is to reuse and to recycle the huge amount of construction and demolition waste (CDW) it generates. Recycled concrete aggregate (RCA) is recognized by EN 206 standard as a legitimate concrete ingredient, but their full potential is far to be used, because of several reasons: availability of natural resources, heterogeneity of CDW, technology and costs issues and mistrust in performances. In Bulgaria, in addition, the national amendment to EN 206 is very restrictive because of lack of national know-how. This study aims to fill the gap and assess the impact of RCA on concrete performance. RCA from three different CDW sources is tested. RCA differs in porosity, water absorption and mechanical characteristics. The performance of recycled aggregate concrete with 30% and 50% replacement of coarse aggregate by RCA is compared to that of natural aggregate concrete. Mix design with two cement quantities and two water/cement ratios are investigated. The higher water absorption of RCA is taken into consideration while producing fresh concrete. The results demonstrate that the quality of primary concrete has certain effect on strength characteristics, E-modulus and water permeability. However, RCA up to 30% does not modify significantly the behaviour of both fresh and hardened concrete. RCA of 50% does not worsen the properties of the concrete, either, but some reduction of performance can be observed. In conclusion, RCA presents a solution for both natural resources preservation and appropriate CDW management.